Studi Literatur: Analisis Penerapan Model Pembelajaran Inovatif Berbasis Pendidikan untuk Pembangunan Berkelanjutan (ESD) dalam Mengembangkan Keterampilan Peserta Didik - Rohmah, Azizatul Nur; Lestari, Nurita Apridiana (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2024)
21st century education faces a major challenge in preparing students to deal with global change. Education for Sustainable Development (ESD) plays an important role in equipping students with the attitudes, skills and knowledge to make sustainable decisions. This article analyzes the application of innovative ESD-based learning models in various disciplines to improve learners' skills. Using the literature study method, the analysis was conducted based on 30 journal articles published in the 2019-2024 period. The results show that the application of ESD-based learning models has a positive impact in improving learners' skills. The most frequently used learning model is Problem Based Learning (PBL), with the most integrated material is Physics, especially the topic of Effort and Energy. The most commonly measured skill is sustainability awareness, which also helps students to be more aware of global sustainability issues. Thus, the integration of ESD in the curriculum can prepare students to face future challenges more effectively, shaping them into individuals who are critical and concerned about the environment and can find sustainable solutions.